Factors Influencing the Incidence of Diabetic Foot Injuries - Husnaeni, Husnaeni; Syaiful, Syaiful; Wahyuni, Sri (Bantayang Omni Cendekia, 2024)
Background: Diabetics who do not pay attention to the type of food consumed will make blood glucose levels uncontrolled, besides that the environment is one of the factors that make health disrupted such as an environment that is often exposed to cigarette smoke, even though cigarettes can interfere with the body's metabolic processes and will affect insulin production. One of the complications that can occur is neuropathy or lack of sensitivity to the nerves which leads to the formation of diabetic foot wounds, when wounds form, they heal or not depending on the wound care process. However, with the principle of wound care, moisture balance has been effective in the wound healing process. Objective: This study aimed to determine the factors that influenced the incidence of diabetic foot injuries in Makassar City. Methods: Quantitative with cross sectional approach. The sample of this study was 34 samples obtained by purposive sampling technique. Data collection was carried out using questionnaires and analyzed using the chi-square test. Results Based on the study, the factors that affect the incidence of diabetic foot injuries are: age obtained p value = 0.015 (<α0.05), Gender obtained p value = 0.020 (<α0.05), Work obtained p value = 0.025 (<α0.05), Long suffering from DM obtained p value = 0.000 (<α0.05), Drug obtained p value = 0.002 (<α0.05), Obesity obtained p value = 0.008 (<α0.05). Conclusion: The conclusion in this study is that factors that influence the incidence of diabetic foot injuries are age, sex, occupation, length of suffering from DM, medication adherence, obesity